Teaching Children to Love Problem Solving ; A Reference from Birth through Adulthood - Germain-Williams, Terri (Singapore : World Scientific Publishing Co. Pte Ltd., 2017)
"This book was developed with the caring and concerned adult in mind and is a one-stop for anyone who would like to help a child develop problem solving thinking. They will become adept at the use of problem solving strategies over the course of their development from birth. For each age range, this book provides developmental information, relevant mathematical concepts, sample problems with multiple solutions, and finally activities to engage with as a family in order to develop mathematical thinking and problem solving skill."--Publisher's website.
Includes bibliographical references (p. 123-124) and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Problem solving -- Study and teaching (Elementary); Mathematics -- Study and teaching (Elementary); Electronic books